Decentred Centre in John Fowles’s The Magus - Matosoğlu, Aleks (Journal of History Culture and Art Research, 2015)
Decentred Centre in John Fowles’sThe Magus Abstract John Fowles’ The Magus (1966) has been the focus of criticism for many years. This study regards the character of Conchis as a decentred “centre” in the structure of the novel and as in the experience of the contemporary humanity. Conchis becomes in the eyes of Nicholas an all-knowing figure, an accumulation of Western thought since the Greek civilization. He produces signs to be read as he himself becomes a body of various signs that construct him as the metaphysical centre that Western thinkers have relied upon. His narration becomes superior to Nicholas’ and he himself becomes only a narrative voice. The voice from the times of Plato has been considered as a direct expression of the thoughts in one’s mind and thus superior to writing that is permeated with the undecidability of meaning in the absence of the speaker and the addressee. In the novel, words as an endless play of metaphors take the place of voice. There is no knowable reality outside the play words or metaphors which is an endless chain of signifiers that lead to other signifiers. Every time Nicholas turns to Conchis to find the centre outside the play of the language, he finds other signifiers. Thus, Conchis as a meaning-making centre is dethroned. He is not the sole operator of the masks that divert from their presumed original target when they are read. Nicholas is just another production of the literary tradition who reads the signs only to produce other signs. Conchis in the beginning of the novel renounces fiction for science but along the course of the novel, we see that words are never reliable whether in fiction or in science.